Peran Kepala Madrasah sebagai Supervisor dalam Peningkatan Kualitas Mutu Pendidikan Islam di Madrasah - Slamet Ariyanto; Wahidmurni; Indah Aminatuz Zuhriyah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to explore the role of madrasah heads as supervisors in efforts to improve the quality of Islamic education in madrasas. The madrasa head plays an important role not only as an administrative leader but also as a supervisor and guide in curriculum development, implementation of learning, and increasing teacher competency. The methodology used in this research is a qualitative approach with data collection techniques through observation, in-depth interviews and documentation studies. The research results show that madrasah heads play a key role in several main aspects: development of relevant and innovative curricula, teacher development through training and classroom supervision, routine supervision of the learning process, effective resource management, formation of a conducive academic culture, assurance of educational quality according to standards, as well as developing students' character with integrity and noble character. The implementation of these roles has been proven to improve the quality of Islamic education in madrasas, create a harmonious learning environment, and produce graduates who are superior in both academic and moral aspects. This research concludes that optimizing the role of madrasah heads as supervisors is the key to improving the overall quality of Islamic education.